'Civilized Dispossession': Corporate accumulation at the dawn of modern capitalism. Issue 12 (December 2022) - Van Lent, Wim; Islam, Gazi; Chowdhury, Imran
Critical scholarship views corporate accumulation – a fundamental driver of capitalism – as inherently dispossessive, involving violence and expropriation. However, dispossession also involves practices of legitimation that are related to coercive violence in complex ways. We examine the roles of dispossession and legitimation practices as constitutive of corporate accumulation. Specifically, we analyse how dispossession is connected to the appropriation of legitimacy as a symbolic resource which justifies and enables violence and expropriation. Taking an historical perspective, we examine a paradigmatic case of corporate accumulation: the Dutch East India Company's monopolization of spices on the Banda Islands (1599–1621). In this process, the Dutch moved from (1) initial instances of legitimation to (2) legitimation to enforce Dutch–Bandanese agreements, to (3) legitimation to enable dispossession of the Bandanese, to finally (4) wholesale dispossession of the Bandanese. These four phases reflect a mechanism that we call 'civilized dispossession', which describes the escalating three-way interplay between Dutch practices of dispossession and legitimation and Bandanese resistance, and which was driven by institutional experimentation and multi-level institutional work. Integrating institutional and critical perspectives, the notion of 'civilized dispossession' provides a novel theorization of corporate accumulation, elucidating the mechanisms by which corporations promote the diffusion of capitalism.